Students’ reading comprehension level and reading demands in teacher education programs: the elephant in the room? - Orellana, Pelusa; Silva, Mónica; Iglesias, Vicente (Frontiers in Psychology, 2024)
Introduction Reading comprehension is considered a key ability for students in teacher education programs. Methods Data from 72 students enrolled in a Chilean school of education was used to estimate the contribution of reading proficiency in first-semester academic performance using regression analysis. Results Reading comprehension made a significant, albeit modest contribution to predict students’ academic performance, after controlling for their scores in the standardized national admission tests and high-school grades. The students’ average reading level was below the level of text complexity required in their first term and, although by their senior year they had made significant progress in reading comprehension, their reading level continued to be lower than text demands. Discussion A qualitative exploration of students’ reading behaviors and attitudes revealed they devoted few hours per week to reading class material and even less time to reading for leisure. Faculty were cognizant of the reading deficits of their students but had few suggestions as to how to address. Future studies in higher education should confirm whether the misfit between reading proficiency and reading demands observed in this school of education is the exception or the rule.